(untitled) (Canadian Oncology Today, 2025)
Deficient mismatch repair (dMMR) or microsatellite instability-high (MSI-H) metastatic colorectal cancer (mCRC), accounting for approximately 4–5% of cases, represents a distinct molecular subgroup with unique therapeutic implications. These malignancies are characterized by a high mutational burden and increased immune cell infiltration, making them particularly responsive to immune checkpoint inhibitors (ICI). Conversely, this subgroup tends to be less sensitive to traditional chemotherapy.